Predicting Significant Factors of Postgraduate Students to Use English Learning Apps in Kunming, China - Wang, Yibo (Scholar: Human Sciences, 2024)
Purpose: This research delves into the determinants that shape the behavioral intention and use behavior of English learning apps among postgraduate students in Kunming, China. The conceptual framework encompasses elements like the perceived simplicity of use, perceived utility, attitude, perceived control over behavior, social impact, behavioral intent, and use behavior. Research design, data, and methodology: The target population encompasses 500 postgraduate students from the top three universities located in Kunming, China. Employing a quantitative methodology, the research engaged a questionnaire as the principal means of data collection. The sampling methodologies employed judgmental, stratified random, and convenience sampling. A preliminary assessment was carried out with 50 participants, analyzed by Cronbach’s alpha. The data were analyzed with confirmatory factor analysis (CFA) and structural equation modeling (SEM). Results: Perceived usefulness significantly impacts attitude. Behavioral intention has a significant impact on use behavior. Behavioral intention is significantly impacted by attitude, but isn’t impacted by perceived behavioral control, and social influence. Additionally, perceived ease of use did not significantly impact attitude and perceived usefulness. Conclusions: The insights gained pave the way for more targeted strategies to enhance app adoption and effective use, with implications for educational institutions, app designers, and policymakers seeking to optimize technology integration in education.